ECCRINE DUCTAL CARCINOMA - Matos, Diogo (2015)
Ductal eccrine carcinoma is a rare and aggressive skin cancer. Its diagnosis implies the exclusion of a primary adenocarcinoma located elsewhere with cutaneous metastization, as the histological and immunohistochemical analysis are not sufficient by themselves. We report the clinical case of a 75-year-old male with a 3 cm width tumor located on the right hemiface, which was excised and whose histology and immunohistochemistry pointed towards an eccrine ductal carcinoma. The complementary investigation showed multiple pleural and pulmonary nodules, as well as neoplastic involvement of the dorsal and lumbar vertebral column. Their histological and immnunohistochemical examination, supplement with the absence of imagiologic findings suggesting a primary tumor in another location, allowed the diagnosis of a metastatic eccrine ductal carcinoma. The patient died 6 months after the initial consultation.